Programa educativo basado en algeplano para desarrollar la competencia resuelve problemas de regularidad, equivalencia y cambio de estudiantes del cuarto grado de secundaria en la Institución Educativa N°60110 Quistococha, San Juan 2022 - Paredes Perea, Vidal (2022)
The objective of the study was to evaluate to what extent the application of the educational program based on the algeplano influences the development of the competence solves problems of regularity, equivalence and change in fourth grade students of the secondary level of the Educational Institution No. 60110 Quistococha, San Juan, 2022. The methodology used in the research was experimental and quasi-experimental design with pre-test and post-test. The population and sample consisted of 64 fourth grade high school students, of which 32 from section A participated in the experimental group and 32 from section B in the control group. According to the results, it was determined that the application of the program based on the algeplano significantly influences the development of translating data and conditions into algebraic expressions, communicating their understanding of algebraic expressions, using strategies and procedures to find general rules, arguing statements about exchange relations and equivalence in fourth grade secondary school students of the educational institution studied, because the value p-value = 0.000 <0.05 was obtained. Significance level: ?=5%. It is concluded that the application of the educational program based on the algeplano significantly influences the development of the competence solves problems of regularity, equivalence and change in the students who participated in the present study.